Advancing dosimetry for Dating Environmental Materials: Development of an ultra-sensitive beta dosimeter system and potential for beta autoradiography. (June 2022) - Martin, L.; Sanderson, D.; Paling, S.; Cresswell, A.; Murphy, S.
Abstract: Beta Dose Rate heterogeneity is a recognized source of uncertainty when applying luminescence dating to heterogeneous samples, such as coarse crystalline rocks and clast-rich sediments. Simulations have shown that a combination of a heterogeneous distribution of minerals and radioactive elements can lead to complex dose distributions, overdispersion and potentially to bias in equivalent dose determinations. However setting realistic conditions for such simulations remains difficult, and there are at present only a few experimental validation cases for such simulated systems. Project ADDEM is investigating means of linking Monte Carlo simulations of dose rate to specific minerals with direct observations using high sensitivity phosphor plates and laser scanning imaging systems in combination with phase mapping. To overcome some of the limitations of autoradiographic imaging of low level beta dose distributions work has been undertaken using Landauer alumina OSL phosphor screens in combination with a laser scanning system developed at the Scottish Universities Environmental Research Centre (SUERC). Preliminary excitation spectra, emission band characterization and time resolved measurements were undertaken, confirming the potential to recording low doses using asynchronous stimulation at 635 nm coupled with blue band detection. Taking advantage of the slow decay of the luminescence signal the scanning equipment has been configured for pulsed stimulation and asynchronous detection to maximise signal to background ratios. Exploratory work was calibrated using a 60 Co facility capable of calibrating doses in the μGy to mGy range. A series of powdered granulite/basalt mixtures of known mean activity and dose rate (Dr) have also been used to calibrate the phosphor screens. To reduce background levels during autoradiographic signal accumulation rock slices are being exposed in the Zeplin shield of the STFC Boulby Underground Laboratory, in an environment which is essentially free from cosmic ray muon background. Simulations have been conducted providing preliminary deconvolution parameters in order to either reconstruct the beta dose rate (β Dr) distribution received by the grains in the sample, or retrieve the radioactive element distributions in the minerals of the sample, providing the data required for representative simulations of β Dr. This paper outlines the spectroscopy and sensitivity verification of the autoradiography system, confirming its prospects for measuring spatially resolved β Dr distributions with single pixel lower detection limit of 130 μGy and spatial resolution of 150 μm. Prospects are outlined. Highlights: The properties of an Al2 O3 :C dosimeter film for beta dose imaging were investigated. A protocol of laser scanning OSL imaging using pulse stimulated OSL was developed. The dosimeter film showed a linear dose response and sub-mGy sensitivity per pixel. A significant background signal can limit the accuracy for low dose measurements. Simulations of beta exposure indicate the need for dose image deconvolution.